Genesis, controls and risk prediction of H2S in coal mine gas - Weidong Xie (Nature Portfolio, 2021)
Abstract Abnormal H2S concentration in coal mine gas is a serious threat to normal mining activities, which has caused serious loss of life and property in many coal mines. This study explores the genesis and influencing factors of abnormal H2S concentration in coal mine gas, taking the Xishan coal mine in the Fukang mining area as a case study. The H2S formation by bacterial sulfate reduction (BSR) is simulated with a bacterial culture experiment and that by thermochemical sulfate reduction (TSR) is simulated with a thermal reduction experiment. The potential for a magmatic genesis is assessed using data regarding the tectonic evolution and history of magma intrusion in the study area. The factors influencing H2S formation and enrichment are then analyzed by a comprehensive consideration of the characteristics of coal, the gas composition, the coal seam groundwater geochemistry and other geological factors in the study area. The results show that the study area meets the necessary conditions for the BSR process to operate and that there is widespread BSR derived H2S. TSR genesis H2S mainly forms in coal fire areas and their vicinity, while there is little contribution from magmatically formed H2S. The concentration of H2S is negatively correlated with the buried depth of the coal seam, the concentrations of CH4, N2 and CO2, and the ash yield; and it is positively correlated with the volatiles yield and total sulfur content. In addition, in areas with abnormally high H2S concentration, the concentration of SO4 2− is obviously lower, HCO3 − + CO3 2− concentration is higher, and the HCO3 −/SO4 2− value is larger than that in non-anomalous areas. Geologically, H2S enrichment is found to be controlled by lithology, tectonism, and hydrogeological conditions. Moreover, the results of predictive modeling show that areas prone to abnormal H2S concentration are generally spatially correlated with coal fire areas. In this study, the genetic types of H2S and the factors controlling their formation and retention are discussed, producing research results that have guiding significance for the prediction and prevention of the coal mine disasters that arises from abnormal H2S concentration.